Public perception of the production and commercialization of genetically modified sweet orange trees (Research, Society and Development, 2021)
Over the past few decades, the production of transgenic food has generated debates around advances in agricultural biotechnology and their social, political, economic, and environmental concerns in the world, and especially in Brazil, a country with a notable prominence for agribusiness. As part of this debate, this study aimed to understand, through the application of online questionnaires to the 318 respondents, the acceptance or rejection of consumers regarding the potential use of genetically modified sweet orange fruit for human consumption and the perspectives for the future release of production at the commercial level. It was observed that there is high acceptance of the consumption of transgenic oranges, but these products will have resistance from part of the population and import markets for possible production and commercialization. However, it was observed that there is a high perspective of the population for transgenics to become an important alternative in the control of the main citrus diseases that drastically affect the productivity of this sector.